2000
DOI: 10.1002/1521-3935(20001101)201:17<2510::aid-macp2510>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Studies on controlled radical polymerisation using 5-membered cyclic PROXYL nitroxides and corresponding alkoxyamines

Abstract: 2,2′,5,5′‐tetramethylpyrrolidine‐N‐oxyl (PROXYL) and derivatives bearing one α‐aryl substituent (Ph, p‐CF3Ph, p‐Me2NPh) were prepared and converted to alkoxyamines by reaction with di‐tert‐butyl peroxalate (DTBPO) and excess styrene. Both the nitroxides (plus DTBPO as a radical source) and alkoxyamines were investigated in the controlled radical polymerisation (CRP) of styrene, and their behaviour was compared to that of TEMPO. Polymerisation mediated by each nitroxide displayed a linear relationship between m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Compound 4 was synthesized according to a similar procedure; 1 to 3 were prepared from styrene, nitroxide and DTBPO according to a literature procedure. [24] In all cases, characterisation data were in accord with literature values.…”
Section: Alkoxyamine Synthesissupporting
confidence: 75%
See 3 more Smart Citations
“…Compound 4 was synthesized according to a similar procedure; 1 to 3 were prepared from styrene, nitroxide and DTBPO according to a literature procedure. [24] In all cases, characterisation data were in accord with literature values.…”
Section: Alkoxyamine Synthesissupporting
confidence: 75%
“…The ESR data alone do not provide an explanation for the differences in polymerisation behaviour of the various alkoxyamines, namely that 3 mediates the polymerisation of styrene significantly faster than that of both 1 [24] and 5 b together with its ability to bring about butyl acrylate polymerisation. [26] In an attempt to rationalize these observations, we examined the decomposition of various alkoxyamines to generate unsaturated species and hydroxylamine (see Scheme 5).…”
Section: Decompositionmentioning
confidence: 86%
See 2 more Smart Citations
“…It has been shown that the activation energy ( E a ) of alkoxyamine homolysis is a good estimate of the value of the bond dissociation energy of the CON bond 32, 33. We28, 32, 34, 35 and others23, 36–42 have shown that the CON bond in alkoxyamines is either strengthened by anomer effects39, 42 due to, for example, a heteroatom bound to the carbon and by polar effects23, 35, 41, 42 due to an electron‐withdrawing group bound to the nitrogen atom or weakened by the steric strain and the polar effects of both alkyl and nitroxyl fragments 23, 27–32, 34, 36. Furthermore, the stabilization of the released alkyl radical and the nitroxyl radical, stabilized by an intramolecular hydrogen bond, also weakens the CON bond 23, 32, 34, 36, 37, 39, 42.…”
Section: Introductionmentioning
confidence: 99%